2018
DOI: 10.1016/s2214-109x(18)30122-0
|View full text |Cite
|
Sign up to set email alerts
|

Can Zika virus antibodies cross-protect against dengue virus?

Abstract: Does immunity after Zika virus infection cross-protect against dengue? Lancet Glob Health 2018; 6: e140-41. 2 De Smet B, Van den Bossche D, van de Werve C, et al. Confirmed Zika virus infection in a Belgian traveler returning from Guatemala, and the diagnostic challenges of imported cases into Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Contemporaneous studies from Brazil and Nicaragua demonstrated evidence of short-term protection from ZIKV infection or development of ZIKV disease associated with recent DENV infection [ 47 , 50 ]. Initial analyses demonstrated a low frequency of cross-neutralization following ZIKV infection, suggesting that ZIKV does not elicit long-lasting cross-protective antibodies against DENV [ 51 , 52 ]. Both protection from and enhancement of dengue severity has been associated with prior exposure to other flaviviruses [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contemporaneous studies from Brazil and Nicaragua demonstrated evidence of short-term protection from ZIKV infection or development of ZIKV disease associated with recent DENV infection [ 47 , 50 ]. Initial analyses demonstrated a low frequency of cross-neutralization following ZIKV infection, suggesting that ZIKV does not elicit long-lasting cross-protective antibodies against DENV [ 51 , 52 ]. Both protection from and enhancement of dengue severity has been associated with prior exposure to other flaviviruses [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…A pattern also found in vivo when rhesus macaques, previously infected with ZIKV, experienced higher viremia and proinflammatory cytokines during a subsequent DENV-2 infection compared to those previously uninfected with ZIKV [ 17 ]. In contrast, a Brazilian study reported a decline in dengue infections following a Zika outbreak, eluding to cross-protection, not enhancement [ 18 ]. However, given that cross-protective ZIKV IgG antibodies wane over time [ 19 ], the remaining cross-reactive antibodies may facilitate adverse ADE mechanisms later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this evidence from DENV sequential infections, it remains poorly understood if the same applies to the time interval between ZIKV–DENV sequential infections. So currently, the role of multiple convalescent periods to ZIKV in the outcome of DENV and other flavivirus infections is in the forefront of discussions based on the limited studies available in experimental models and a lack of characterized human prospective cohorts of this scenario yet 27,4345 .…”
Section: Introductionmentioning
confidence: 99%